2019
DOI: 10.1002/jbmr.3824
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preclinical Development of TransCon PTH, an Investigational Sustained-Release PTH Replacement Therapy for Hypoparathyroidism

Abstract: Hypoparathyroidism (HP) is a condition of parathyroid hormone (PTH) deficiency leading to abnormal calcium and phosphate metabolism. The mainstay of therapy consists of vitamin D and calcium supplements, as well as adjunct Natpara (PTH(1‐84)). However, neither therapy optimally controls urinary calcium (uCa) or significantly reduces the incidence of hypercalcemia and hypocalcemia. TransCon PTH, a sustained‐release prodrug of PTH(1‐34) in development for the treatment of HP, was designed to overcome these limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The results of a phase I trial with TransCon PTH in healthy volunteers demonstrated a markedly prolonged half-life of free PTH of ~60 hours 60 . Notably, a net increase in bone resorption with TransCon PTH administration has been observed 59 . Although this could theoretically lead to a primary hyperparathyroidism-like profile, increased resorption could have a salutary effect to decrease the high bone mineral density and increase the low bone turnover rate of hypoparathyroidism.…”
Section: Current and Future Therapiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of a phase I trial with TransCon PTH in healthy volunteers demonstrated a markedly prolonged half-life of free PTH of ~60 hours 60 . Notably, a net increase in bone resorption with TransCon PTH administration has been observed 59 . Although this could theoretically lead to a primary hyperparathyroidism-like profile, increased resorption could have a salutary effect to decrease the high bone mineral density and increase the low bone turnover rate of hypoparathyroidism.…”
Section: Current and Future Therapiesmentioning
confidence: 99%
“…A potential new therapy is TransCon PTH, an inactive prodrug of PTH(1-34) that is designed to achieve an infusion-like profile by liberating active PTH in a sustained fashion 59 . PTH(1-34) is transiently bound via a linker to a chemically inert carrier that shields PTH from binding to the PTH type 1 receptor (PTHR1) and prolongs the peptide’s circulation half-life due to reduced renal clearance 59 .…”
Section: Current and Future Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Trans-Con or other long-acting PTH molecules are designed to have longer half-lives and a persistent biological effect. Figure created by Dr Guido Zavatta from published data ( 12 , 13 , 14 , 21 , 46 ). …”
Section: Adjunctive Therapy With Available Pth Analogsmentioning
confidence: 99%